**Answer:**

915.69549 m

306.1968 m

**Explanation:**

t = Time taken

u = Initial velocity

v = Final velocity

s = Displacement

a = Acceleration = 3.25 m/s²

g = Acceleration due to gravity = 9.81 m/s²

Height is given by

Total distance the canister has to travel is 230+76.1968 = 306.1968 m

Time to reach the max height

Time taken to reach the ground is

Total time taken would be 3.9413+7.9 = 11.8413 seconds

**The rocket is 685.69549+230 = 915.69549 m from the launchpad.**

**The total distance is 230+76.1968 = 306.1968 m**

The higher the frequency, the higher or sharper (the musical term if you prefer such things) the pitch is.

The** upward force **exerted on the board by the support is mathematically given as

**Fu= 764.8 N **

<h3>What is the upward force exerted on the board by the support?</h3>

Generally, the equation for is mathematically given as

Considering that the **Net Force** on the system is null

The weight of the **children **plus the weight of the board equals the upward force imposed on the **support**.

The upward force

Fu= 440 + 272 + 52.8 N

**Fu= 764.8 N **

In conclusion, he **upward **force exerted on the board by the **support**

**Fu= 764.8 N **

Read more about **force **

**brainly.com/question/13191643**

#SPJ1

Despite current has a magnitude and a direction, like vectors, it is a scalar because it doesn't obey laws of vector addition. For instance, if we consider a junction of

in a circuit, and two currents entering this junction, we know that the resultant current is just the algebraic sum of the two currents, not the vector sum, so it is not a vector quantity.

**Answer:**

(a)T= M2 × g, (b)T= (M1 + M2)g, (c)T= M2 (a + g) and (d)T=(M1 + M2) (a + g)

**Explanation:**

M1 is hanged upper and M2 is lower at Rest.

(a) For M2

T2 = Weight of the Body M2= M2 × g

(b) T1 = Weight of the Body M2 + Weight of the Body M2

T1 = M1 g + M2 g = (M1 + M2)g

M1 is hanged upper and M2 is lower at accelerated upwards ( F = T - W)

(c) For M2

⇒T = M2a + M2g = M2 (a + g)

(d) For M1

T = (M1 + M2) a + (M1 + M2) g

⇒ T = (M1 + M2) (a + g)